EFEKTIFITAS PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN GUNA MENCEGAH TERJADINYA PENGULANGAN TINDAK PIDANA (Studi pada Lembaga Pemasyarakatan klas IIA Padang) - Besse Patmawanti (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
The guidance function has been carried out in an integrated manner between theTrustees and those who are fostered and the community to improve the quality ofcorrectional facilities. It is intended that the wargabinaan be aware of their mistakes andimprove themselves so as not to repeat the criminal acts in the future. Pancasila as theideal foundation of the correctional system, mentions the existence of balance andharmony both in human life as a person, and in relations with society in relation to nature,as well as relations with God. The implementation of prisoner guidance to prevent theoccurrence of repetitions of crime is guided by Law No. 12 of 1995 concerning Prisoners,prisons strongly uphold the human rights of every human being, guidance provided to theassisted people is only intended so that the inmates will no longer repeat criminal actsafter free from criminal sanctions imposed upon him for acts he has committed so thatafter being returned to the community, the assisted citizens can become good individualsand obey the applicable law. The obstacle faced by the correctional institutions in carryingout guidance to prisoners is over capacity in terms of the number of prisoners not inaccordance with the capacity provided, the number of employees who are not inaccordance with the number of prisoners and another obstacle is the placement ofprisoners.